Spousal Caregiver Resilience: Husbands’ Experiences in Caring for Wives with Schizophrenia - Yudhaningrum, Iswaranisita; Afiatin, Tina (Faculty of Psychology, Universitas Gadjah Mada, 2025)
This study aims to explore the resilience experiences of husbands who take on the role of spousal caregivers for wives diagnosed with schizophrenia. A qualitative descriptive approach was employed to capture a rich, straightforward, and low-inference account of participants’ caregiving experiences without imposing predetermined theoretical interpretations. A four-phase thematic analysis was conducted to analyze the data. Five male participants, aged 30–60 years, were included in the study. Each had been a spousal caregiver for more than five years. The findings revealed seven themes: onset transition, adaptation to caregiving tasks, maintaining the marriage, spiritual discipline, active participation in community and society, challenges from family and the wider community, and contribution to society. In addition, the study found that cultural factors significantly influence the dynamics of resilience, particularly in decision-making processes. This research can support health professionals and academics in understanding the lived experiences of male spousal caregivers. Nonetheless, the study is limited by its small, homogeneous sample of Javanese Muslim caregivers from a local community in Yogyakarta, which may limit the generalizability of the findings. Future research should consider more diverse samples and use mixed-method approaches to broaden insights into resilience across different caregiving contexts, including those involving child-rearing and other vulnerable family settings.